Editorial for the Special Issue on “Multidisciplinary Insights on Bone Healing (Volume II)” - Alexandre Anesi; Mattia Di Bartolomeo (Biology)
As the population ages and differences among sexes and age groups become more pronounced, the research on bone healing and damage mechanisms continues to advance, with evaluation conducted in both pre-clinical and clinical settings [...]